El Domicilio Fiscal y el Acto de Notificación: Aspectos Doctrinarios y su Regulación en la Normatividad Tributaria - Baca Zavaleta, Jesús Joel (2018)
The current research is leaded to establish, based on the dogmatic and the jurisprudential criteria, the unconstitutionality of the tenth final and complimentary disposition of the Executive decree Nº 981, and the necessity of its repeal since this injured the fundamental rights it is said The due Process of Law both in the administration and the compelled rights such us right to defense, contradiction and the access to resources; for this purpose, it has been taken into account, holistically , the theoretical development of all involved legal institutions. For this reason, it stars from the premise that the Political Constitution is the fundamental issue around which all the legal system revolve, as a result of this, the current legal system must have coherence related to its constitutional text, the same that incorporates the Due Process to the essential content of the fundamental rights taking part as a source of validity and effectiveness in all the process. On the other hand, it is postulated that the taxing power, embodied in the creation of procedural rules devoted to regulate the administrative actions inside the tax procedures must be done in base on criteria of coherence with the sense of the Constitution designing the appropriate rules that constitute true procedural safeguards through which the balance is keeping among the public interest, the act of imposition of taxes and the right of taxpayer to participate in such proceedings taking into account the respect to the right of defense. Finally, considering the point of view that the plausible affectation that verifies through the results obtained for the current research, as a result of the product of the analysis of the Resolutions of the Fiscal Tax Court given in application of the disputed rules moreover Its immediate repeal of the necessity of legislative changes that incorporate a new regulation about the tax residence of the subjects whose state in the taxpayer’s registry is their definitive derognition, and to confer prosecutorial powers to the Administration in the process of constitutionality.